Dengue Hemorrhagic Fever with Acute Fulminant Hepatitis: A Case Report - M Adi Firmansyah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Dengue virus is estimated to cause over 100 million infections throughout the world annually. Although dengue infections can have a wide range of clinical pictures, atypical manifestations have been described recent years. The liver is a susceptible organ affected in dengue infection. Mild liver dysfunction is common in cases of dengue infection but severe liver function impairment and even encephalopathy are rare. The following is a case report of dengue hemorrhagic fever (DHF) with acute fulminant hepatitis. A 43-year-old woman has fulminant hepatitis on day 3 of treatment. Her AST level increased dramatically from 363 U/L to 3,246 U/L. The causes of other hepatitis infection has been excluded. Her dengue IgM-antibody level was reactive. Level of dengue IgM antibody reactive. Clinical improvement experienced by patient after supportive therapy and administration glisirizin or Stronger Neo-Minophagen-C (SNMC).